PENGARUH SENAM HIPERTENSI TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Hendi Rifqi Alhafis; Dewi Rury Arindari (Jurnal Kesehatan : Jurnal Ilmiah Multi Sciences, 2019)
One in ten adults in the world has high blood pressure. World Health Organization (WHO) year (2016) called hypertension as "an epidemic that spreads beyond. Management of hypertension from it all can be prevented through nonpharmacological therapy that is by exercising regularly. According to data obtained from the Alang-Alang Lebar Public Health Center in Palembang it is known that the number of hypertensive sufferers in 2018 is 1,781 people. The purpose of this study was to determine the effect of hypertension exercise on blood pressure reduction in the Alang - Alang Lebar Puskesmas Work Area in 2019. This research method uses Quasy Experiment with a Non-Equivolent Control Group. The population of this study was all hypertension sufferers in the Work Area of Alang-Alang Lebar Health Center in Palembang in January - March 2019 as many as 84 people. The sample used in this study was a portion of the population, namely some patients with hypertension in the Alang-Alang Lebar Puskesmas Work Area in Palembang totaling 30 respondents. Data analysis uses univariate and bivariate analysis. The results showed an average value of blood pressure in the control group before hypertension was 160.56/100.56 mmHg and the intervention group averaged 159.4/96.6 mmHg. After hypertension gymnastics, the mean blood pressure in the control group was 160/99.44 mmHg and in the intervention group the average value was 136.11/93.89 mmHg. The results of the bivariate analysis revealed that there was an effect of hypertension exercise on the reduction of blood pressure in the Work Area of Palembang Alang-Alang Lebar Health Center in 2019 p value = 0,000. The results of this study can be used as one of the considerations in providing alternative non-pharmacological therapies in non-communicable disease (PTM) programs at the Alang-Alang Lebar Health Center in Palembang.